Resiliência jurídica: para pensar a inovação do direito a partir de uma perspectiva sistêmica - Flores, Luis Gustavo Gomes (Universidade do Vale do Rio dos Sinos, 2014)
This thesis aims to research the theme "Innovation capability of Law from the idea of Rresilience in a systemic perspective". To do so, this theme was delimited through research on the ability of Law to be Innovated from two basic perspectives, namely: a systemic-constructivist epistemology, and the symbolic dimension of Resilience as a "reflexive strategy". This reflection was formulated to answer the following question: what are the conditions for thinking resiliently the Innovation in Law in a complex society? Or better, would it be possible to think Innovation in Law considering the redefinition of Resilience in Law from a systemic perspective? The main objective of this work was to develop a way of observing to allow Law to understand the conditions and operations that would be necessary to think Innovation in Law when faced to a complex environment. Its specific objectives were structured in three stages. The first specific objective was to understand the dogmatic presuppositions of Law and fundamental features of a constructivist epistemology as an alternative to overcome the legal dogmatic. The second specific objective was to understand the contribution of the concept of Resilience for Law (when considered as an autopoietic system). The third specific objective was to develop a reflection in the sense of thinking Innovation in Law, from the so-called Juridical Resilience. Its methodology was the systemic-constructivist method, a perspective that considers reality as a construction of an observer. It involves a complex second-order observation, assuming a set of theoretical categories that are characteristics of PragmaticSystemic Matrix. It was concluded that through the Pragmatic-Systemic Matrix, which presupposes a systemic- constructivist epistemology and reframing Resilience in Law, a new form of observation could arise, Juridical Resilience, which is a reflective strategy for reducing complexity constructively, as an alternative to think about Innovation in Law in contemporary society.
Keywords: Teoria dos sistemas; Sociologia; Inovação do direito; Resiliência jurídica; Systems theory; Sociology; Innovation in law; Juridical resilience; ACCNPQ::Ciências Sociais Aplicadas::Direito